2018
DOI: 10.3892/or.2018.6739
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑mRNA integrated analysis based on a case of well‑differentiated thyroid cancer with both metastasis and metastatic recurrence

Abstract: The incidence of well-differentiated thyroid cancer (WDTC) is rapidly increasing. Poor survival follows distant metastasis (DM) and recurrence. In the present study, we aimed to analyze the expression alterations in different stages of WDTC and the regulatory mechanism of DM and the recurrence of DM. A male patient diagnosed with follicular thyroid cancer and distant metastasis in the eleventh thoracic vertebrae received total thyroidectomy and the removal of a metastatic lesion. A local relapse was found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…To explore the functions of proteins that are dysregulated in CLM, we used DAVID (Database for Annotation, Visualization and Integrated Discovery) analysis software to classify the gene ontology of the 2,170 significantly altered proteins in MT tissues 19 (Figures S3A–S3C). Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of differentially expressed proteins 20 revealed that metabolic pathways were altered in the MT samples, with 323 significantly differentially expressed proteins (14.88%) involved in metabolic pathways (Figure S3D), which suggests that metabolism-related pathways may play important roles in the liver metastasis of CRC 21, 22, 23, 24Figure 1Differently Expressed Protein and mRNA-Protein Correlation Analysis(A) Numbers of differently expressed proteins (≥2-fold difference; p < 0.05 with a FDR q value < 0.05) between the 44 CRC and paired PN samples, and the 23 MT and 21 NM samples.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the functions of proteins that are dysregulated in CLM, we used DAVID (Database for Annotation, Visualization and Integrated Discovery) analysis software to classify the gene ontology of the 2,170 significantly altered proteins in MT tissues 19 (Figures S3A–S3C). Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of differentially expressed proteins 20 revealed that metabolic pathways were altered in the MT samples, with 323 significantly differentially expressed proteins (14.88%) involved in metabolic pathways (Figure S3D), which suggests that metabolism-related pathways may play important roles in the liver metastasis of CRC 21, 22, 23, 24Figure 1Differently Expressed Protein and mRNA-Protein Correlation Analysis(A) Numbers of differently expressed proteins (≥2-fold difference; p < 0.05 with a FDR q value < 0.05) between the 44 CRC and paired PN samples, and the 23 MT and 21 NM samples.…”
Section: Resultsmentioning
confidence: 99%
“…STRING (version: 11.0; ) was used to analyze the interaction relationships between differential proteins ( 17 ). The species was set to human and the import gene set was set to all degrees.…”
Section: Methodsmentioning
confidence: 99%
“…Protein-Protein Interaction (PPI) Network and Module Analysis of Dif-mRNAs STRING (version: 11.0; https://www.string-db.org/) was used to analyze the interaction relationships between differential proteins (17). The species was set to human and the import gene set was set to all degrees.…”
Section: Library Construction and Sequencingmentioning
confidence: 99%
“…The interaction between DEG-encoded proteins was analyzed by STRING (version 10.0; https://string-db.org/cgi/input.pl ) database. 57 The input gene set was set as all DEGs, and the species was set as human. To get the most closely related interaction pairs, we set the parameter PPI score to 0.99 (high confidence).…”
Section: Methodsmentioning
confidence: 99%